Perencanaan Ruang Terbuka Publik di Natas Lehong, Kabupaten Manggarai Timur sebagai Tempat Rekreasi - Jostar Jovandri Noari Parera; I Made Sukewijaya (Fakultas Pertanian, Universitas Udayana, 2024)
Natas Lehong is one of the public open spaces in East Manggarai Regency which has an area of 2,86 Ha. Natas Lehong is a public open space that has a main function as a ceremonial field. In addition to its main function, Natas Lehong has another supporting function as a recreational facility. However, the supporting function cannot run well due to the lack of facilities that support recreational activities such as jogging tracks, park benches, playground areas, food and beverage stalls, and other supporting facilities. This research aims to plan public open space in Natas Lehong, Borong City, East Manggarai Regency as a place for recreation. This research uses a survey method with descriptive analysis and uses a qualitative research approach. The basic concept of this research is